(untitled) (Vietnam Journal of Community Medicine, 2026)
A randomized controlled trial was conducted at the National Hospital of Odonto-Stomatology, Hanoi, enrolling 64 patients (ASA physical status I–II, aged 18–60 years) to compare preoperative oral carbohydrate loading with Carberas versus standard preoperative fasting before general anesthesia for third molar extraction. The intervention group received Carberas (600 mL on the evening before surgery and 300 mL ≥2 hours before induction), whereas the control group fasted from 10:00 p.m. on the night before surgery. Results: Age, body mass index (BMI), operative time, and the number of teeth extracted did not differ significantly between groups (all p>0.05). Thirst and dry mouth scores were significantly lower in the intervention group than in the control group both preoperatively (p < 0.01) and postoperatively (p < 0.01). Blood glucose levels were similar between groups before and after surgery (p > 0.05) and remained within normal limits despite a mild postoperative increase. Gastric antral cross-sectional area (CSA) and estimated gastric residual volume were comparable between groups (p > 0.05). No patient had a gastric volume >1.5 mL/kg, and no aspiration events were observed. Conclusion: Preoperative oral carbohydrate loading with Carberas is safe and improves patient-reported comfort in third molar extraction under general anesthesia.